Structural and Antimicrobial Evaluation of Silver Doped Hydroxyapatite-Polydimethylsiloxane Thin Layers. (7th March 2017) - Iconaru, S. L.; Chifiriuc, M. C.; Groza, A.
Abstract : An Ag:HAp (x A g = 0.5) powder was deposited by thermal evaporation technique as coating on a silicon substrate previously covered with a polydimethylsiloxane (PDMS) layer. The Ag:HAp-PDMS layers were characterized by Scanning Electron Microscopy (SEM), Energy Dispersive X-ray Spectroscopy (EDS), and Fourier Transform Infrared Spectroscopy (FT-IR). By infrared spectroscopy analysis, the phase composition of the Ag:HAp-PDMS layers was investigated. The antimicrobial activity of Ag:HAp-PDMS layers was tested against Escherichia coli, Staphylococcus aureus, and Candida albicans microbial strains. The microbial activity decreases significantly for the surveyed time intervals on Ag:HAp-PDMS layers.